Remote monitoring to address obesity by physical education professionals: an integrative review (Research, Society and Development, 2021)
Introduction: The world is in a pandemic situation due to COVID-19, an infectious disease that affects humans caused by the coronavirus, called SARS-CoV-2. Considering the increase in obesity during the pandemic in the Brazilian population, it is necessary to expand the capacity to assistance from the physical educator, seeking new health promotion strategies through guidelines for changing lifestyle habits. Objective: To identify which types of remote monitoring are used to perform remote physical exercise in obese individuals. Method: This is an integrative literature review carried out during the month of June 2020 in the National Library of Medicine database (PubMed), using the following descriptors: “Obesity”, “Biomedical Technology”, “Mobile applications”, “Health promotion”, “Disease prevention”, “Telemonitoring”, “Physical exercise”. The inclusion criteria defined for the selection of articles were: original articles, literature reviews (systematic, integrative or narrative) and experience reports, published between April 2014 and April 2020, in English and Portuguese, available in full and that presented the description of the steps / methods used for the intervention with remote physical exercise by physical educators. The exclusion criteria were: duplicity of articles, editorials, conference proceedings, case study and reflection articles; intervention by another professional. Results: The types of remote monitoring most used by physical educators in the treatment of obesity were: smartphone apps, text messages, e-mails, letters (sent by mail) and website. Conclusion: Remote interventions are effective for weight loss in the short term. In addition to weight loss, remote monitoring is favorable for increasing the frequency of physical activity and other behavioral changes in obese individuals.